Mechanistic investigations on the catalytic transfer hydrogenation of lignin-derived monomers over Ru catalysts: theoretical and kinetic studies - Khan, Tufeil Sartaj; Singh, Dheerendra; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Dhepe, Paresh Laxmikant (ACS Sustainable Chemistry & Engineering, 2021)
The hydrodeoxygenation (HDO) reaction of oxygenated compounds such as lignin-derived phenolics is well studied using molecular H-2 as a hydrogen source, yet the use of high pressures discourages its use on an industrial scale. As an alternative, the catalytic transfer hydrogenation (CTH) pathway provides in situ hydrogenation species, which reduces the need for the high-pressure infrastructure required when molecular hydrogen is used. Nevertheless, this strategy is scantly studied, and in lieu with this, herein we report the kinetic and mechanistic investigations of the CTH strategy for the HDO of guaiacol, phenol, anisole veratrole, and eugenol to their respective products. For potential commercialization purposes, low loading of metal, milder reaction conditions, and high selectivity toward desired products with a high H/C ratio were considered while designing catalysts (0.5 wt % Ru on SiO2-Al2O3, SiO2, Al2O3-acidic, Al2O3-basic, and Al2O3-neutral) for these reactions. As high as 74% cyclohexanol yield from guaiacol was achieved at 225 degrees C in the presence of isopropyl alcohol (IPA) as the hydrogen source and over the Ru/Al2O3-acidic catalyst reduced at 150 degrees C. A detailed kinetic study is carried out to understand the interaction of the substrate and intermediates with the catalyst and the influence of reaction parameters on the product formation. It was observed that the cisisomer of 2-methoxycyclohexanol rapidly undergoes further conversion than the trans-isomer. The experimental observations are substantiated through density functional theory (DFT) studies on Ru(0001) and guaiacol molecule complexes. DFT studies indicate that the adsorption of the cis-isomer is more exothermic as compared to that of the trans counterpart, and the underlying electronic factors are elucidated using charge density difference and density of states plots.
Keywords: catalytic transfer hydrogenation; Cyclohexanol; DFT; Hydrodeoxygenation; kinetics; lignin monomers; Supported metal catalysts